Changes in turbulent flow structure over rough-bed under combined wave-current motions. Issue 3 (1st September 2016) - Singh, Santosh Kumar; Debnath, Koustuv; Mazumder, Bijoy S.
Abstract: This paper presents the result of an experimental study carried out in a laboratory flume to investigate the interaction of surface wave and unidirectional current over cube-mounted rough-bed. The cubes were made of wood and were positioned at the channel-bed with different spacing. The study particularly focuses on the changes induced in the spatially averaged velocity profile, turbulent intensity and Reynolds stress due to the superposition of waves of different frequencies on current-induced flow. The spatially averaged velocity profile shows two distinct regions: the linear or exponential distribution below the roughness tops and logarithmic profile above the roughness top. The profile of streamwise turbulent intensity is similar to that of current-only flow except in the region near the water surface. In contrast, the profile of bottom-normal turbulent intensity is almost constant over the entire depth. Below the roughness crest, the form-induced stress changes significantly with switching from negative to a positive value with change in roughness spacing, but is not affected much by the presence of surface wave.